Persepsi Remaja Pelaku Tindak Pidana terhadap Gaya Pengasuhan Orangtua - Gerry Olvina Faz (Syams: Jurnal Kajian Keislaman, 2021)
Adolescence is a transition to adulthood. One issue identified during this developmental stage requiring a need to deal with is unlawful conduct. Data from Komisi Perlindungan Anak Indonesia (KPAI) reveal that unlawful conducts committed by younger people increasingly is growing every year in Indonesia. It’s caused by, among others, problematic parenting. Parenting plays important role during adolescence and highly correlates to behavioral problems. This research was conducted towards youths involved in Juvenile delinquencies in Juvenile Detention Center/ Lembaga Pembinaan Khusus Anak (LPKA) Palangka Raya, to find out their perception toward parental care before they undergo programs in LPKA Palangka Raya. The research aims to analyze parenting problems facing juvenile offenders that can be used as inputs for parents to improve their parenting skills. This research employed qualitative method and data collected through Focus Group Discussion (FGD) involving four people as subjects. The research revealed parenting problems in applying control and acceptance. Parents of research subjects tended to show neglectful, permissive, and authoritarian parenting. In addition, subject’s parents imposed hostile rule enforcement and inconsistent parenting.